Synthesis and biological evaluation of novel Δ2-isoxazoline fused cyclopentane derivatives as potential antimicrobial and anticancer agents1. Issue 5 (13th May 2015) - Prajapti, Santosh Kumar; Shrivastava, Shweta; Bihade, Umesh; Gupta, Ajay Kumar; Naidu, V. G. M.; Banerjee, Uttam Chand; Babu, Bathini Nagendra
<x xml:space="preserve">Abstract</x> Novel Δ2-isoxazoline fused cyclopentane derivatives have been synthesized and evaluated for their antimicrobial and anticancer activities.